Are the music and the choreography for “The Flower Festival” Pas de deux by Paulli and Bournonville? - Jürgensen, Knud Arne (Danish Yearbook of Musicology, 1995)
Are the music and the choreography for The Flower Festival Pas de deux by Paulli and Bournonville? Since the creation in 1858 of August Bournonville's and Holger Simon Paulli's Flower Festival Pas de deux this dance has achieved its rightful place in the international repertory of classical ballet. It represents one of Bournonville's most happy blends of the Italian-Franco-Danish ballet cultures of his century, and perhaps, even more so, than has hitherto been thought. In connection with a current research project on the original sources and the performing history of Bournonville's ballets in his own lifetime, some unknown sources have been discovered that have shed new light on the genesis of this dance duet. They raise the question whether the Flower Festival Pas de deux can, in faet, still be considered an original work by Bournonville and Paulli, or instead perhaps should be regarded as a "re-created" dance, based on an earlier work by artists from a completely different artistic milieu than the Biedermeier artistic world normaIly connected with Bournonville. Through the examination of the existing musical sources for Bournonville's 1856 Vienna staging at the Kärnthnerthor Theatre of his 1842 ballet Napoli, some unknown facts about this production have come to light. They prove that the music for what in 1858 became The Flower Festival Pas de deux was originally composed in Vienna by the Austrian composer, Mathias Strebinger, and first performed in Act III of Napoli to choreography by the Italian dancer, Lorenzo Vienna. These practices of musical borrowing and the rearranging of ballet scores by foreign composers and choreographers were very common in the preceding century and many striking examples of these practices can be found in the Bournonville repertoire. The article discusses these aspects by focusing, in particular, on the genesis of The Flower Festival Pas de deux. This dance documents how Bournonville made an immediate mental note whenever he heard ballet music outside Denmark and then used it later, with the help of Paulli or other Danish composers, in his own ballets in Copenhagen. Moreover, the article reveals that a great part of what we hitherto have considered to be an expression of a specificaIly Danish ballet culture in the Bournonville repertoire is, in reality, either a descendent from or a direct product of contemporary ballet music written by prominent south and central-european choreographers and composers. Thus, much of Danish ballet music from the middle of the 19th century is actually more of a development of foreign composer's contributions to this field than it is an expression of a special school of Danish ballet music.